2019
DOI: 10.3991/ijoe.v15i11.10647
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence: A Review and Lessons for Developing Countries

Abstract: Most of the time, complete adherence to prescribed medication is a big step towards recovery from either chronic or acute diseases, but patients often are unaware of the adverse effects that could arise from inconsistency in adherence. The inability of patients to adhere to prescription can affect the potency of some effective therapies known to treat many conditions, and passive compliance may result in the development of resistant to drug causing a need for treatment modification. Shockingly, more than half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…55 – 57 Implementing other strategies such as offering medication home delivery service and prescription pick-up reminders could also be effective in facilitating medication access and improving adherence rates and ultimately lead to better health outcomes for patients. 58 60 Furthermore, affordability and out-of-pocket medication costs may have played a role in the present study's low medication adherence rate, as insurance companies do not cover expenses for medications that are prescribed through the Anat platform. 30 Exploring options for reducing the cost of medications such as working with insurance companies to cover prescriptions issued from Anat system and utilizing generic medication name when possible can help address financial barriers that may contribute to primary non-adherence.…”
Section: Comparison With Other Studies and Explanationmentioning
confidence: 95%
See 1 more Smart Citation
“…55 – 57 Implementing other strategies such as offering medication home delivery service and prescription pick-up reminders could also be effective in facilitating medication access and improving adherence rates and ultimately lead to better health outcomes for patients. 58 60 Furthermore, affordability and out-of-pocket medication costs may have played a role in the present study's low medication adherence rate, as insurance companies do not cover expenses for medications that are prescribed through the Anat platform. 30 Exploring options for reducing the cost of medications such as working with insurance companies to cover prescriptions issued from Anat system and utilizing generic medication name when possible can help address financial barriers that may contribute to primary non-adherence.…”
Section: Comparison With Other Studies and Explanationmentioning
confidence: 95%
“…By establishing a strong patient–provider relationship and actively involving patients in their treatment plans, healthcare providers can improve patient outcomes and reduce the burden of medication non-adherence on the healthcare system. 41 , 60 , 62 , 63 …”
Section: Comparison With Other Studies and Explanationmentioning
confidence: 99%
“…Nonadherence is particularly high among patients with chronic diseases, with hypertensive patients accounting for nearly 50% of cases. By 2025, the prevalence of hypertension is expected to increase by 30% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In hospitals, the occurrence percentage of medication error for ordering is 56%, administration is 34%, transcribing is 6% and 4% for dispensing [4], [5]. Although hospital statistical data show that most healthcare institutions have computerized medical data, the Institute of Medicine (IOM) reported that a patient can be subjected to multiple medication error during the clinical process [6]. In addition, each year the United States have approximatively 1.5 million of preventable medication errors.…”
Section: Introductionmentioning
confidence: 99%